Caracterización Fitoquímica De Metabolitos Secundarios Presentes En Anredera Cordifolia “Daizako” Y Su Posible Potencial Actividad Hipoglucemiante - Tapias Casas, Danny Bernardo (Universidad Antonio Nariño, 2023)
Diabetes mellitus is a disease characterized by insulin resistance, thus generating peaks of hyperglycemia, the complications derived from sustained hyperglycemia are well known, from cardiac hypertrophy to renal failure, and it is estimated to have a prevalence in Colombia of more than 1,600,000 inhabitants. However, it is also important to note that this increase is more marked in South American countries and the lower middle class, and it is expected that by the current lifestyles, these figures will rise in the coming years